2017
DOI: 10.1590/s1677-5538.ibju.2015.0666
|View full text |Cite
|
Sign up to set email alerts
|

Nutcracker Syndrome: laparoscopic external stenting of the renal vein (“the shield technique”)

Abstract: Nutcracker syndrome refers to the complex of clinical symptoms caused by the compression of the left renal vein (LRV) between the abdominal aorta and the superior mesenteric artery, leading to stenosis of the aortomesenteric portion of the LRV and dilatation of the distal portion. Hematuria, proteinuria, flank pain, varicocele and pelvic congestion may occur, occurring more frequently in young adults. Conservative management, might be the option whenever it is possible. When surgical treatment is required, cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, the current literature remains insufficient insofar as indications, contraindications, complications, and outcomes for this type of intervention are concerned. 12,13 The therapeutic benefits of ES could surpass lumen patency and local hemodynamics. 14 In 1996, Angelini et al showed that ES can improve morphological and biological features of those vessels supported by ES.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current literature remains insufficient insofar as indications, contraindications, complications, and outcomes for this type of intervention are concerned. 12,13 The therapeutic benefits of ES could surpass lumen patency and local hemodynamics. 14 In 1996, Angelini et al showed that ES can improve morphological and biological features of those vessels supported by ES.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments include clinical management in most cases, and weight gain might be of benefit ( 5 ). Nephrectomy, reno-caval re-implantation or shunts (open, laparoscopic or robotic), external stents (open, laparoscopic or robotic) and endovascular venous stents have also been reported ( 4 , 6 , 7 ). Since surgical alternatives are invasive and outcomes are not outstanding ( 8 ), endovascular stents have emerged with the appeal of a less invasive procedure.…”
mentioning
confidence: 99%